Do minimum wages improve self-rated health? Evidence from a natural experiment - Lucas Hafner; Benjamin Lochner (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
In this paper we analyze whether the introduction of the general minimum wage in Germany in 2015 had an effect on workers' self-rated health. To study this question, we use survey-data linked to administrative employment records and apply difference-in-difference regressions combined with propensity score matching. This approach enables us to control for a vast set of possibly confounding variables. We find on average significant improvements of self-rated health for individuals who are affected by the reform. Our results indicate, that a significant reduction of weekly working hours potentially drives this result. – – Wir untersuchen ob die Einführung des allgemeinverbindlichen Mindestlohns in Deutschland in 2015 einen Effekt auf die selbsteingeschätzte Gesundheit der Arbeitnehmer hatte. Um diese Frage zu beantworten nutzen wir Befragungsdaten, die mit administrativen Beschäftigungsdaten verknüpft wurden. Wir führen Differenzen-in-Differenzen Schätzungen mit Propensity-Score Matching durch, was uns erlaubt eine Vielzahl von potentiellen Störgrößen zu berücksichtigen. Wir finden heraus, dass die Mindestlohneinführung eine signifikante Verbesserung der selbsteingeschätzten Gesundheit zur Folge hatte. Unsere Ergebnisse deuten darauf hin, dass dieser Effekt durch sinkende Wochenarbeitszeit zurückzuführen ist.
Keywords: I10; I18; J38; 330; Minimum Wage; self-rated health; natural experiment